Estrutura populacional do siri candeia achelous spinicarpus (Crustacea, portunoidea) no litoral norte paulista - da Silva, Thiago Elias [UNESP]; Taddei, Fabiano Gazzi; Bertini, Giovana [UNESP]; Andrade, Luciana Segura; Teixeira, Gustavo Monteiro; Fransozo, Adilson [UNESP] (Pensoft Publishers, 2017)
The swimming crab Achelous spinicarpus is commonly captured as a “by catch” of the shrimp fishery. This study evaluated some aspects of the population structure of A. spinicarpus, such as sex-ratio and size classes’ frequency distribution. A shrimp trawler equipped with double-rig nets was used to capture the swimming crabs at Ubatuba and Caraguatatuba areas, northern coast of São Paulo state, Brazil. A total of 1,057 individuals were collected in Ubatuba, including 598 males (525 juveniles and 73 adults) and 459 females (379 juveniles and 80 adults, including 15 ovigerous crabs). In Caraguatatuba 5,112 individuals were collected, of which 3,138 males (2,638 juveniles and 500 adults) and 1,974 females (1,746 juveniles and 228 adults, including 29 ovigerous crabs). The sex-ratio favors the number of males in both regions, probably because females have the habit of occupying deeper regions. The size classes’ frequency distribution shows polymodality for both sexes, except for males in Ubatuba. This is the result of some age groups among the juveniles, which migrate to shallower areas, being affected by the fishing activity. Adults have the habit of staying in deeper areas characterized by colder waters.
Population structure of the swimming crab Achelous spinicarpus (Crustacea, Portunoidea) in São Paulo northern coast, Brazil
Keywords: Brachyura; Bycatch; Decapoda; Sex-ratio; Size distribution